FOSTERING THE ALPHA GENERATION: A CHARACTER EDUCATION BASED ON JAVANESE UNGGAH UNGGUH (ETIQUETTE) CULTURE IN MADRASAH IBTIDAIYAH - Adisti, Aprilian Ria; Rozikan, Muhamad (UIN Sunan Kalijaga Yogyakarta, 2021)
This paper portrays the implementation of character education based on Javanese unggah-ungguh (etiquette) in Madrasah Ibtidaiyah Karanganyar, using 24 students from 5th-grade who were mentioned as the alpha generation in 2020. Generally, this generation refers to children born after 2010 in this digital era. The unggah-ungguh is one of the Indonesian ancestral heritages that must be preserved, as though it may originate from Java, it strongly represents the culture of the country’s society. Six (6) characters of Javanese unggah-ungguh were used in this research as indicators, which are tata krama (manners), lembah manah (relent), andhap asor (humility), tepa slira (tolerance), grapyak (friendliness), and ewuh-pekewuh (reluctance). This study was descriptive qualitative research that focused on observing the realization of character education based on this culture, using observation, interview, survey, and documentation as the data collection instruments. As reviewed from the affective theory of Krathwohl Taxonomy, the education character based on Javanese unggah-ungguh has influenced three-component domains of affective attitudes, which are in the level of receiving or attending, responding, and valuing. Lastly, the result showed that implementing character education based on this culture has truly shaped a better personality for students in Madrasah Ibtidaiyah Karanganyar as the alpha generation.